Mixotrophic plankton and Synechococcus distribution in waters around Svalbard, Norway during June 2019 - Parli, Bhaskar V; Bhaskar, Jane T.; Jawak, Shridhar; Jyothibabu, R.; Mishra, Neelima (Polar Science, 2021)
In order to understand the influence of summer conditions (extended daylight, warmer temperature, increased meltwater, increased suspended load and nutrient chemistry) on the distribution of phytoplankton (diatoms & flagellates) and picoplankton community in the surface waters off Svalbard, samples were collected from 6 locations around Svalbard onboard National Geographic Explorer vessel. Additionally, satellite data was obtained for surface temperature, chlorophyll a (chl a) and total suspended mass (TSM). Stations Gnålodden (S1), Bellsund (S4), Open Ocean (S5), and Magdalenefjorden (S6) were along the western coast while stations Storfjorden (S2) and Western Storfjorden (S3) were on the eastern side of Svalbard and open to Barents Sea. Phytoplankton abundance ranged from 4 to 49 × 103 cells L−1 and were dominated by dinoflagellates such as Perdinium, Protoperidinium, Dynophysis, Gyrodinium, Gymnodinium and Torodinium species while diatoms (Navicula) were found only in colder polar waters (S5 and 6). Flowcytometry data showed the predominance of Synechococcus sp. and its abundance varied from 0.8 × 105 cells L−1 (S5) to 4.3 × 105 cells L−1 (S4). The distribution of Synechococcus was positively correlated to nitrate (r = 0.838) and chl a (r = 0.915) while phytoplankton abundance had no correlation with chl a or nitrate. A weak positive linear relation between Synechococcus and TSM suggests that melting of glaciers and influx of land run-off may be playing some role in increasing the picoplankton load in these waters. The predominance of mixotrophic dinoflagellates alongwith ciliates like Strombidium in these waters suggests that grazing of picoplankton as well as bacteria might fuel their carbon demand. Our data reflected post-spring bloom conditions wherein Synechococcus were the dominant primary producers and microbial loop might play an important role in sustaining the mixotroph population. journal article